(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Alkylphenols have been synthesised in high yield by the alkylation of phenol with olefins (C6-C8) in the presence of sulphuric acid. The effects of the variation of temperature, molar ratio of phenol to olefin, time of reaction, concentraction and amount of sulphuric acid have also been studied on the reactions. Keywords: Alkylation, Phenol, Sulphuric Acid doi: 10.3329/bjsir.v44i1.2722 Bangladesh J. Sci. Ind. Res. 44(1), 131-136, 2009